Application of the Certainty Factor Method to Diagnose Escherichia Coli Bacteria in Refilled Drinking Water - Agustina Simangunsong; Penda Sudarto Hasugian (Jurnal Info Sains : Informatika dan Sains, 2020)
An expert system is a software package or computer program package that is intended as a provider of advice and aids in solving problems in certain areas of specialization, such as problems in medicine, education, and so on.The development of expert system development in the field of bacteriology is one thing that is expected to improve the quality of human life. One of them is to apply an expert system using the Certainty Factor method to diagnose escherichia coli (e-coli) bacteria in refilled drinking water. This study aims to increase knowledge about how to make an inference engine to control the process of identifying solutions using the Certainty Factor method and to design an expert system application using the Certainty Factor method to diagnose Escherichia coli bacteria in refill drinking water.